(untitled) (International Journal of Physiotherapy, 2026)
Background: In recent years, technological advances in total knee arthroplasty (TKA) have made procedures more precise, reducing complications and accelerating recovery. Although the latest techniques offer several advantages, there are still doubts regarding their true functional efficacy and the level of patient satisfaction they provide. Methods: A retrospective study involving 1,076 patients, distributed as follows: 366 (34.0%) conventional instrumentation (CI), 591 (54.9%) Patient-Specific Instrumentation (PSI), and 119 (11.1%) robotics. All functional outcomes were assessed preoperatively and 90 days postoperatively. Bivariate analyses were performed using ANOVA and the Kruskal- Wallis test, with a significance level of p < 0.05. Results: At 90 days, the robotics maintained the greatest flexion range (p = 0.001) and outperformed the PSI and IC in the walking test (350.3 ± 102.1 vs. 312.5 ± 92.9 and 283.8 ± 84.8, respectively; p < 0.001). On the WOMAC test, PSI performed best (14.5 ± 10.6; p = 0.001), with IC and robotics showing similar results (p = 0.974). There was no difference between the groups in absolute gains. In terms of percentage gains, PSI was higher in WOMAC compared to IC (p=0.041) and robotics (p<0.001). Satisfaction was identical between the instrumentation methods (p=0.199). Conclusion: Absolute gains in functional evolution and satisfaction appear to be independent of the surgical technique, although PSI appears to offer improvements in functional activities. Given the still-limited experience with robotic surgery, the functional benefits and long-term satisfaction remain inconclusive.